Ambipolar Organic Phototransistors with p‐Type/n‐Type Conjugated Polymer Bulk Heterojunction Light‐Sensing Layers. (18th November 2016) - Nam, Sungho; Han, Hyemi; Seo, Jooyeok; Song, Myeonghun; Kim, Hwajeong; Anthopoulos, Thomas D.; McCulloch, Iain; Bradley, Donal D. C.; Kim, Youngkyoo
Abstract : Ambipolar organic phototransistors with sensing channel layers, featuring p‐type and n‐type conjugated polymer bulk heterojunctions, exhibit outstanding light‐sensing characteristics in both p‐channel and n‐channel sensing operation modes.